2020
DOI: 10.3390/urbansci4020015
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation, Proximity, and Social Innovation: Three Ingredients for Industrial Medium-Sized Towns’ Renewal?

Abstract: Over several decades, medium-sized industrial towns have suffered from a combination of economic and political processes: Deindustrialization, metropolization, and withdrawal of public services. After two decades in which they have been somewhat neglected (in favor of metropolises), there have recently been State and European public policies aimed at them. Medium-sized cities are not homogeneous and present several trajectories. Based on quantitative approach in France, we highlight the very diverse socio-econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 54 publications
0
1
0
1
Order By: Relevance
“…Industrial culture can be approached as a catalyst for combating negative socio-economic changes and building resilience in a deindustrialised context, since articulating (post)industrial narratives can generate trust and collective directions of economic development (Pike, 2020). The concept has already been used in social innovation research, where it has been recognised to mobilise actors to create new solutions to existing social needs (Gros-Balthazard & Talandier, 2020;Tiran et al, 2019). A case study of a transforming industrial city revealed that industrial values such as camaraderie, solidarity, and equality can be translated into volunteering and innovative social service activities that provide social care and security to citizens (Kozina et al, 2021).…”
Section: Discussion and Conclusion: Identifying Additional Research Possibilitiesmentioning
confidence: 99%
“…Industrial culture can be approached as a catalyst for combating negative socio-economic changes and building resilience in a deindustrialised context, since articulating (post)industrial narratives can generate trust and collective directions of economic development (Pike, 2020). The concept has already been used in social innovation research, where it has been recognised to mobilise actors to create new solutions to existing social needs (Gros-Balthazard & Talandier, 2020;Tiran et al, 2019). A case study of a transforming industrial city revealed that industrial values such as camaraderie, solidarity, and equality can be translated into volunteering and innovative social service activities that provide social care and security to citizens (Kozina et al, 2021).…”
Section: Discussion and Conclusion: Identifying Additional Research Possibilitiesmentioning
confidence: 99%
“…Nyseth et Hamdouch (2019) y voient des pratiques et activités permettant de faire face à des enjeux sociaux ou de répondre aux besoins sociaux de la population d'un territoire. Ils arrivent à la même conclusion qu'une multitude de chercheurs : l'IS permet d'identifier les besoins d'une communauté (Bartels, 2017;Gros-Balthazard et Talandier, 2020;Howaldt et Schwarz, 2010;Ricciardelli et collab., 2020;Thompson, 2019). Une nuance est toutefois apportée par Cajaiba-Santana (2014) : répondre à un besoin social ne constitue pas automatiquement une innovation sociale.…”
Section: Une Réponse à Des Besoins Sociauxunclassified